Miriam’s Dance as Embodied Prophecy (Exodus 15:20–21) - Portier-Young, Anathea E. 1973- (2024)
The discursive labeling of Miriam as prophet constructs her drumming, dancing, and singing as prophetic acts; her actions simultaneously reshape the prophetic role as participatory, creative, and relational. A theoretical frame drawn from dance studies and the new materialist philosophy of Karen Barad supports the argument that the drumming, dancing, and singing of Miriam and the women of Israel in Exod 15:20-21 are a prophetic performance that gives shape and expression to the subjectivity and agency of God and people after the moment of transition between the victory at the Reed Sea and the journey to Sinai. The collaborative prophetic activity of drumming, dance, and song celebrates divine dynamism and responsiveness, enacts healing for a traumatized people, and entrains their bodies for life in covenant community.